An Effectiveness of RNA interference therapies in reducing urine and plasma oxalate levels among patients with primary hyperoxaluria- A systematic review: RNA interference therapies in primary hyperoxaluria- A systematic review (Pakistan Journal of Kidney Diseases, 2025)
Background:Primary hyperoxaluria is a rare genetic disorder of hepatic oxalate over production. Standard of care was largely supportive with hyperhydration, urinary alkalinization and pyridoxine. RNA interference therapies have recently shown promising results.Material and Methods:The systematic review was prospectively registered with PROSPERO and followed PRISMA guidelines. Pubmed, EMBASE and CENTRAL were searched from January 1974 to July 2024 for randomized controlled trials and single arm intervention studies on use of RNAi therapies in primary hyperoxaluria.Results:We found 127 records across the databases, with 12 of them included in the final analysis. A total of 140 patients were enrolled in Lumasiran (9 trials) and Nedosiran (3 trials). Most studies demonstrated a significant reduction in the oxalate burden. Injection site reaction was the most common adverse event with a largely acceptable safety profile. Quality of studies assessed through ROB-2 and ROBINS-I showed a low risk of bias.Conclusion:This systematic review emphasizes the effectiveness and safety of RNA interference therapies, Lumasiran and Nedosiran, in treating primary hyperoxaluria by lowering urinary and plasma oxalate levels.